Breach of Notarial Deed for Peace under Indonesian Civil Law Perspective - Maulin, Yola; Sandra, Eidy; Kusmayanti, Hazar (Jurnal Media Hukum, 2019)
The peace agreement resulted from an out of court mediation process can be made in the form of either an authentic deed or underhand deed. This paper discusses the application of the principle of ‘ne bis in idem’ in lawsuit relating to the breach of the notarial deed for peace and the legal strength of notarial deed for peace based on the Civil Code and the Civil Procedure (HIR). Data in the form of primary and secondary legal materials were collected through both library research and field work. It is found that with regards to Article 1917 of the Civil Code and Article 130 paragraph (2) the Civil Procedure (HIR), the principle of ‘ne bis in idem’ is not contained in a lawsuit against the breach of notarial deed for peace. It is also found that the legal strength of the notarial deed for peace is the same as the authentic deed as outlined in Article 1870 of the Civil Code and Article 165 of the Civil Procedure (HIR).